Pengembangan Buku Ajar Ilmu Gizi Olahraga: Studi Motivasi dan Hasil Belajar - Lufthansa, Lutfie; Susilo, Sigit; Zaini, Moh; Kusmawati, Wiwik; Pawitra, Paulus Rah Adi; Anugraini, Asri Putri (Journal Sport Area, 2019)
The goal of the research is to improve students’ motivation and to enhance students’ learning result. The development of the teaching book on Sports Nutrition refers to the 4D models which consist of 4 stages, namely Define, Design, Development, and Disseminate, modified to be adapted to this research. The analysis of quantitative descriptive is used to process quantitative data that gained from the expert validation sheet (material, language, media) to know the advisability of the textbook. Product trials are carried out by comparing previous learning motivation data and after textbooks are used by students. Then the learning outcomes data were analyzed to determine the N-Gain value between pretest and posttest. Based on the results of expert validation, it is known that the Sports Nutrition textbook is proper and can be used as a lecture textbook with a material validation score of 91.6% (valid), language validation of 87.5% (valid) and 80% media validation (sufficient valid). The results of analysis of students learning result data are obtained an average pretest score of 6.86 and the average post-test score is 7.73. In conclusion, there is an increase of 0.87 and to be gotten N-Gain of 0.3 with the medium category. Based on the results of the research, it can be concluded that the development of Sports Nutrition textbooks increases students' motivation and improves student learning outcomes Physical Education and Recreation IKIP Budi Utomo Malang.